Teaching Voiced and Voiceless Sounds in EFL Classrooms: A Conceptual Review of Challenges and Pedagogical Strategies - Aswar Aswar; Abdul Rahman R. (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2026)
The teaching of pronunciation, particularly the distinction between voiced and voiceless sounds, remains a critically underexplored domain within English as a Foreign Language (EFL) pedagogy. This article presents a conceptual review grounded in three theoretical pillars: phonological theory, first language (L1) transfer theory, and intelligibility-based pronunciation instruction. Three primary challenges are identified: L1 phonological interference, articulatory and perceptual difficulty, and limited phonological awareness among learners and teachers. Four evidence-based pedagogical strategies are proposed: explicit phonological instruction, minimal pair practice embedded in communicative tasks, auditory discrimination training, and technology-assisted pronunciation tools. The article argues that the intelligibility principle should guide instructional priorities, with high-functional-load contrasts such as /s/–/z/, /t/–/d/, and /f/–/v/ receiving primary attention. Implications are drawn for EFL teachers, curriculum designers, and teacher training programs.